(untitled) (Physical Education, Health and Social Sciences, 2025)
Brucellosis is a contagious and zoonotic disease, affecting human and animals equivocally. It is a seriously neglected disease in underdeveloped countries, causing heavy financial losses in the livestock sector in terms of abortion, and a decrease in milk production. To better cope with socioeconomic impact of brucellosis, this study was conducted in district Swabi with the aim to detect brucellosis in high-risk human population through serological Rose Bengal plate test, Serum plate agglutination test, Enzyme-Linked Immunosorbent Assay, and molecular Polymerase chain rection techniques with respect to different risk factors and clinical history. A total of 250 blood samples (n=250 each from Human) were collected through predesigned questionnaire and were processed for detection of brucellosis through different techniques in Veterinary Research Institute, Peshawar. Detection of brucellosis frequency was performed through SPAT, RBPT, Indirect ELISA (IgM, IgG) and PCR as 12.4, 10.4, 11.6, 12 and 9.6% respectively. A numerical difference was observed through detection of different tools, but the difference was statistically non-significant (p>0.05). The present research contributes to the existing prevalence data concerning brucella infection in humans and emphasizes the benefits and effectiveness of the molecular technique of PCR compared to serological tests.